HEURISTIC EVALUATION ANALYSIS USING THE 10 NIELSEN RULE USABILITY METHOD ON THE KAI ACCESS APPLICATION - Muhammad Syarqim Mahfudz; Febrina Agusti; Sefa Az Zahra; Berliana Rahma Dhini (Proceeding of International Conference on Science, Health, And Technology, 2022)
KAI Access is the official application owned by PT Kereta Api Indonesia (Persero) for ticket cancellations, changing ticket schedules, purchasing local trains, purchasing train tickets 1 hour before departure, e-boarding passes. Based on the user rating on the Play store, which is 3.3 out of 5 stars. In this study using 10 Nielsen's usability rules, with the aim of analyzing whether the KAI Access application can be said to be good or not. Task Analysis which is classified as efficient enough because the value of the lost ness level is only 0.26651869414146. It was found that from 6 of 10 Jacob Nielsen heuristic evaluations, errors were found to minimize the users memory load, feedback, shortcuts, prevent errors, help and documentation, consistency. The 10 principles of usability that need to be improved in this KAI Access application are the Minimize the users memory load type and the Minimize the users memory load type with the same severity rating 3, namely major with a fixed rating of 2, requiring some effort to fix.